The Use of Lean Six Sigma Methodology to Improve Efficiency in Waste Bank Operations and Its Contribution to The Circular Economy - Syallaby, Muhammad; Hardini, Septa (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
Waste banks are innovative solutions in community-based waste management that support circular economy principles. However, many waste banks face various operational constraints such as process inefficiency, waste of resources, and low utilization of technology. This research aims to apply the Lean Six Sigma methodology  to improve the operational efficiency of waste banks and analyze its contribution to the circular economy. With the DMAIC (Define, Measure, Analyze, Improve, Control) approach, the study was conducted through field observations, interviews, and process efficiency analysis at waste banks in South Sumatra Province. The results show that Lean Six Sigma is able to identify points of waste and improve efficiency indicators such as process time, space utilization, and sorting quality. This efficiency has a positive impact on increasing the recycling volume and economic value of waste products. This study shows that Lean Six Sigma integration  supports the transition to a more sustainable waste management system.